The Link between ICT4D and Modernization Theory - Kunst, Marlene (Global Media Journal - German Edition, 2015)
For some decades western institutions have shared an enormous enthusiasm for Information and Communication Technologies for Development (ICT4D). Nevertheless, despite the field’s ever-increasing importance, research on it remains fragmented and lacks a theoretical foundation. By establishing a link between ICT4D and Modernization theory as one of the major development models, this paper aims to add some theoretical reflections to the body of existing research. Initially, a literature review of the most significant authors of Modernization theory serves as a theoretical base. Subsequently, empirical findings are systematized and embedded in the theoretical framework. The leading question is, whether ICT4D is connected to Modernization theory’s main lines of thought, both in theory and in the field. Modernization theory was chosen as a reference point, as even though it has frequently been marked as outdated, some argue that ICT4D has brought about its revival: Led by a technocratic mindset, actors in the field have indeed assumed ICTs to be context-free tools, which is one of the reasons why ICT4D has so far not been an unmitigated success. As there is a lack of systematic research on ICT4D, this paper is explorative in nature. It is certainly beyond the author’s scope to make any definite statements on how development cooperation has hitherto handled ICT4D, as the field is too complex. Instead, light will be shed on some trends that can be identified in the field of ICT4D to date.